Foreign direct investment in sub-Saharan Africa: Beyond its growth effect - Hassen Abda Wako (Research in Globalization, 2021)
This study relates foreign direct investment (FDI) to economic growth, institutional quality and manufacturing value added, using panel data techniques that allow for parameter heterogeneity and non-stationarity. The results confirm that economic growth, institutional quality, and natural resources, each play a positive role in attracting FDI. Besides, institutional quality is itself affected by these variables: economic growth enhances institutional quality, FDI is detrimental to certain aspects. The evidence also reveals the existence of 'institutional' resource curse. Furthermore, FDI has contributed to the 'premature' deindustrialization of the region, except in a few cases where it is non-resource seeking. While confirming established results, the study also identifies detrimental institutional and deindustrializing effects of FDI which have hitherto been overlooked. A policy implication is that countries should be selective on the type of FDI they try to attract by weighing its positive growth effect against its deindustrializing and adverse institutional effects.
Keywords: F21; F23; O14; O43; 330; FDI; Economic growth; Institutions; Deindustrialization; sub-Saharan Africa